(untitled) (London Journal of Medical and Health Research, 2023)
In 1976 Edward Evarts "The languages of the brain introduction to neuropsychology" studied the behavior of certain neural mechanisms which are activated in the motor cortex and provide a mirror image of the force field external (orthostatism, variations of inertia in the actions). This type of neuron acts during muscle contraction. The confirmation came from the experiences made with monkeys who were trained to manipulate levers to which various weights were connected which opposed the pressure action. The recordings show that these brain areas are activated before the lever is pressed and that the electrical activity (electromyography) is proportional to the amount of force, pressure, necessary to overcome the resistance which, in the containers with the food, was greater. The information on the pressure to be exerted (choice of the task and execution) is provided by the tension that arises from the adjustment, a kind of pre-regulation, which takes place in the agonist and antagonist muscles before the gesture (reaction), determining a state of cocontraction for effect of the Feed-forward control mechanism (in this phase the system oscillates like the needle of the balance, which subsequently stops on the exact weight). The aim is to contrast the weight with an adequate stiffness (consistency of the contractile structures) in times of the order of 0 milliseconds, to compensate for the delay of the proprioceptive feed-backs. It is probable, as Prof. Nikos Makris, that a kind of resonance is created between the oscillation frequencies of the peripheral structures with those of the brain areas. From our study it emerges that a different approach to fatigue, considered as a signal, and not a value, has allowed us to modulate the work proposal, both at a sporting and rehabilitation level, in order to choose what to suggest, depending on a measurable and objective data obtained on resilience. This data allows you to choose whether to increase the load or reduce the tension, in order to reduce the entropy of the system, and therefore reduce energy expenditure in both the athlete and the neurological patient.